The Existence of Training Participants an Integrative Perspective - Ihsan, Muhammad; Effendy, Moh. Hafid (Maharot : Journal of Islamic Education, 2024)
This study aims to explore and analyze the existence of training participants at Pondok Pesantren Mambaul Ulum Bata-Bata from an integrative perspective, which combines traditional religious education with practical skills training. Using a quantitative method, data was collected through questionnaires from 120 students participating in the training program, 58% of whom were male students and 42% female students. The average skill score before training was 55, while after participating in the training it increased to 85 (p < 0.01). This demonstrates the effectiveness of the training program in equipping students with skills relevant to the workforce. The religious understanding score increased from an average of 65 to 78 (p < 0.05) after integration with the training, indicating that the training program did not reduce the intensity of religious education. Pearson correlation test showed a significant positive relationship (r = 0.72, p < 0.01) between the level of student involvement in the training program and their skill improvement. The higher the student involvement in training, the higher the practical skills they acquired. The results show that the training program has a significant impact on students' readiness to face the modern world while strengthening their religious education. Further analysis indicates a positive relationship between the intensity of student involvement in training and their skill improvement.